Wilhelm Müller's Lyrical Song-Cycles : Interpretations and Texts - Kung, Isabella (Book collections on Project MUSE., 2020)
Fuzzball is queen of her home, where her "subjects" do her bidding and make sure she is groomed, fed, and entertained, calling her name "nooo Fuzzball" all day long--but one day they leave the house, and when they do not return promptly Fuzzball starts to worry, and finally, in a panic, she resolves to be a more benevolent queen, and maybe redecorate the house to show her feline approval of her staff.